Comoros : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2000)
In this study, the following statistical data are presented in detail: GDP at current market prices; prices of export crops; production and consumption of electricity; indicators of tourism activity; indicators of population, education, and employment; monetary survey; summary statement of the central bank; structure of interest rates; balance of payments; volume and value of principal exports and imports; breakdown of the government wage bill; external debt outstanding by creditors; summary of tax system; consolidated government expenditure; wage bill developments by ministry; and so on.